METHODOLOGY OF SITE-SPECIFIC SEISMIC HAZARD ANALYSIS FOR IMPORTANT CIVIL STRUCTURE - Masyhur Irsyam; Donny T. Dangkua; Dyah Kusumastuti; Engkon K. Kertapati (Institute of Research and Community Outreach - Petra Christian University, 2007)
Note from the Editor The Indonesian archipelago is one of the most active tectonic zones in the world. Therefore to design an important (and dangerous) structure such as a nuclear power plan knowledge of the seismicity of the site is very important. This could be achieved by doing a site-specific seismic hazard analysis. A site-specific seismic hazard analysis is required in the design state in order to determine the recommended seismic design criteria of the structure. A complete and thorough explanation of the methodology to do a site-specific seismic hazard analysis is presented in this Technical Note Abstract in Bahasa Indonesia :